2005
DOI: 10.3171/foc.2005.18.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Management of medically refractory trigeminal neuralgia in patients with multiple sclerosis

Abstract: Object Trigeminal neuralgia (TN) is a painful disorder that frequently causes lancinating, electrical shock–like pain in the trigeminal distribution. Common surgical treatments include microvascular decompression (MVD), radio-surgery, and radiofrequency ablation, and complete pain relief is generally achieved with a single treatment in 70 to 85% of cases for all modalities. In a subset of patients with multiple sclerosis (MS), however, the rates of surgical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 25 publications
1
22
1
3
Order By: Relevance
“…Nevertheless, the possibility of additional nervevessel conflict in MS patients should be kept in mind. Microvascular decompression is associated with a favourable response in approximately 50% of patients [Monstad, 2007;Patwardhan et al 2006;Cheng et al 2005]. The major problem with microvascular decompression in this patient population is the observation that TN often occurs bilaterally and bilateral posterior fossa craniotomies entail a greater risk [Berk, 2001].…”
Section: Treatment Of Trigeminal Neuralgia In Multiple Sclerosismentioning
confidence: 99%
“…Nevertheless, the possibility of additional nervevessel conflict in MS patients should be kept in mind. Microvascular decompression is associated with a favourable response in approximately 50% of patients [Monstad, 2007;Patwardhan et al 2006;Cheng et al 2005]. The major problem with microvascular decompression in this patient population is the observation that TN often occurs bilaterally and bilateral posterior fossa craniotomies entail a greater risk [Berk, 2001].…”
Section: Treatment Of Trigeminal Neuralgia In Multiple Sclerosismentioning
confidence: 99%
“…В тех случаях, ко-гда клиника классической НТН сопровождается чувствительным дефицитом, используют термин чувствительная тригеминальная нейропатия [331,423]. У больных рассеянным склерозом также наблюдается НТН, которую многие авторы относят ко вторичной НТН [63,74,154,158,169,170,184,340,354,365,366,378].…”
Section: от истоков к современному взгляду на патогенезunclassified
“…If the analysis is done in those series that compare classic trigeminal neuralgia and neuralgia associated to multiple sclerosis, some authors reported worse results in cases of multiple sclerosis (Brisman 2000a;Cheng, 2005;Morbidini-gaffney, 2006;Verheul, 2010;Young, 1998). Other manuscripts did not report significant differences in pain control between classic trigeminal neuralgia and neuralgia secondary to multiple sclerosis (Cheuk, 2004;Petit, 2003;Regís, 2009;Riesenburger, 2010;;Rogers, 2000).…”
Section: Association With Multiple Sclerosismentioning
confidence: 99%